2012
DOI: 10.7763/ijbbb.2012.v2.70
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Water Saving Irrigation and Nitrogen Fertilizer on Rice Production in Paddy Fields of Iran

Abstract: Abstract-Rice production in Iran needs to increase to feed a growing population whereas water for irrigation is getting scarce. There are 230000 ha paddy fields in Guilan province in north of Iran. About 73% of paddy fields irrigated by Sepeedrood dam. Shortage of water for rice production will be a problem in near future. In order to investigate the best irrigation regime and nitrogen level an experiment was conducted in split plot based on completely randomized block design with 3 replications at the rice re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
2
4
0
2
Order By: Relevance
“…These results were hold true in the two studied seasons. These results were in agreement with that obtained by Abou khalifa (2010) and Ashouri (2012).…”
Section: I-growth Characterssupporting
confidence: 93%
See 1 more Smart Citation
“…These results were hold true in the two studied seasons. These results were in agreement with that obtained by Abou khalifa (2010) and Ashouri (2012).…”
Section: I-growth Characterssupporting
confidence: 93%
“…It can be also found that H1 hybrid produced the greatest plant height and root depth at all the studied stages followed by H3 hybrid while H2 hybrid gave the least. These data are in agreement with those reported by El-kallawy (2002), Abou khalifa (2010), Ashouri (2012) and Bunnag and Ppngthai (2013).…”
Section: I-growth Characterssupporting
confidence: 93%
“…While, it recorded significantly higher yield than irrigation once every 13-14 days and irrigation once every 16-17 in aerobic rice (Murali, 2009). Grain yield was statistically the same under 8 days intervals and continuous flooding however, water consumption decreased by about 18% under 8 days interval, but the lowest grain yield were of 11 days interval (Ashouri, 2012 andAshouri, 2014).…”
Section: Introductionmentioning
confidence: 80%
“…Rice likes soil water regime from field capacity to shallow submergence in which relatively high percolation loss is inevitable in coarse textured soils [1] [2]. However, irrigations at 6 -8 days interval can also assure good crop under proper choice of variety and management conditions [1] [3]- [5].…”
Section: Introductionmentioning
confidence: 99%